Distinguishing two species of Cavernicola (Hemiptera, Reduviidae, Triatominae) with matrix-assisted laser desorption ionization time-of-flight mass spectrometry - dos Santos Souza, Éder [UNESP]; Fernandes, Richard Perosa [UNESP]; Galvão, Cleber; de Paiva, Vinícius Fernandes; da Rosa, João Aristeu [UNESP] (Elsevier, 2019)
The blood-sucking insects of the subfamily Triatominae are vectors of Chagas disease, the most impairing protozoan parasitic infection in Latin America. Among the five tribes known in the subfamily, one of the least studied is Cavernicolini. It has only two species within Cavernicola genus (Barber, 1937), little is known about the biochemistry of the species of this genus, therefore, using MALDI-TOF MS we provide a better understanding of the two species and differentiates them. The distinction was made by the different spectral profile of the species, where C. lenti presents unique signals in many regions, while the C. pilosa shows high-intensity signals and m/z in high bands. The application of digital mass spectrometry combined with chemometric methods was able to accurately distinguish two species of the genus Cavernicola.
Keywords: Cavernicola; MALDI TOF; Mass spectrometry